Investigating the Effect and Potential Mechanism of Rhamnetin 3-O-α-Rhamnoside on Acute Liver Injury In Vivo and In Vitro - Dandan Deng; Borong Zhao; Hong Yang; Songsong Wang; Ziying Geng; Jiangtao Zhou; Guane Yang; Liwen Han (Pharmaceuticals)
Background/Objectives: Rhamnetin 3-O-α-rhamnoside (ARR) is a major flavonoid of the herb Loranthus tanakae Franch. & Sav., which has been used for treating liver diseases in China. However, the protective effect of ARR on the liver has not been reported. Methods: Zebrafish larvae were used as a visual animal model, and liver injury was induced by thioacetamide (TAA) for an acute liver injury (ALI) model. The hepatoprotective activity of ARR was evaluated by assessing liver morphology, liver function indices, oxidative stress, and the mRNA expression levels of inflammation-related genes in the zebrafish model. Additionally, the ROS level, inflammatory factors, and protein expression related to the IKKβ/NF-κB signaling pathway were measured to investigate a potential mechanism of ARR in HepG2 cells. Results: ARR ameliorated TAA-induced growth retardation, reduced liver injury phenotypes, and decreased oxidative stress in the zebrafish. ARR was also able to lower ROS levels in HepG2 cells, effectively inhibit the overactivation of the IKKβ/NF-κB signaling pathway in pathological conditions, inhibit NF-κB p65 translocation from the cytoplasm to the nucleus, and reduce the release of intracellular inflammatory factors. Conclusions: ARR showed significant protective activity against TAA-induced liver injury in in vivo and in vitro models, and its potential mechanism was closely related to the IKKβ/NF-κB signaling pathway.